2000
DOI: 10.1023/a:1007159031000
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Follistatin is a secreted protein, which functions as an antagonist of different members of the TGF-beta superfamily, including activin and bone morphogenetic proteins. Expression of follistatin is tightly regulated during mouse development both spatially and temporally. In order to study the regulation of follistatin expression in the mouse embryo we have cloned and analyzed part of the 5' flanking region of the murine follistatin gene. Primer extension and RNase protection assays demonstrate that the murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Primer extension analyses confirmed that both ␣T3-1 and primary rat anterior pituitary cells preferentially utilize the "␣" transcription start site and to a lesser extent the "␤" and "␥" sites 4 previously identified from studies of granulosa, P19 and F9 embryonic carcinoma cells (35,36). An upstream fragment equivalent to Ϫ2864 to ϩ136, relative to the transcription start site of the rat follistatin gene, failed to confer activin inducibility onto the basic pGL2 luciferase reporter.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Primer extension analyses confirmed that both ␣T3-1 and primary rat anterior pituitary cells preferentially utilize the "␣" transcription start site and to a lesser extent the "␤" and "␥" sites 4 previously identified from studies of granulosa, P19 and F9 embryonic carcinoma cells (35,36). An upstream fragment equivalent to Ϫ2864 to ϩ136, relative to the transcription start site of the rat follistatin gene, failed to confer activin inducibility onto the basic pGL2 luciferase reporter.…”
Section: Discussionsupporting
confidence: 68%
“…A luciferase reporter construct that incorporates the Ϫ757/ϩ136 fragment of the rat follistatin gene is activated by a combination of cAMP and TPA (35,36). In L␤T2 cells, the same fragment is a target of GnRH (37) but not of activin A in ␣T3-1 cells (38).…”
mentioning
confidence: 99%
“…Based on a genetic epistasis experiment, Fst acts downstream of WNT4 [24]. Furthermore, expression of mouse Fst is dependent upon a consensus β-catenin LEF/TCF binding site in the promoter region [46], [47], and expression of Fst was lost in the β-catenin cKO ovary [18], placing Fst downstream of β-catenin. FST is known to bind activins with high affinity, therefore preventing activins from activating their receptors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EGR-1 may exert its suppressive eect on tumorigenicity via transcriptional regulation of the TGFb gene. Since growth regulation by TGFb is completely abrogated in cells expressing the adenoviral E1A proteins (de Groot et al, 1995), EGR-1 may not be able to exert its growth inhibitory eect. In analogy, prostate carcinomas express elevated levels of TGFb (Royuela et al, 1998), but prostate carcinoma cells are insensitive to growth inhibition by TGFb (Cipriano and Chen, 1998).…”
Section: Discussionmentioning
confidence: 99%